From Balance Sheets to Market Performance: How Internal Efficiency and Economic Conditions Shape Shareholder Value in Indonesian Major Banks - Arya Pradipta; Jagat Prirayani (Eduvest - Journal of Universal Studies, 2025)
This study investigates how internal efficiency and external macroeconomic conditions jointly shape the profitability and shareholder value of Indonesia’s major banks under the KBMI 3 and KBMI 4 classifications during the post-COVID-19 period (2020–2024). Using a quantitative–causal explanatory design and panel data regression, the research analyzes quarterly financial and macroeconomic data from 15 publicly listed banks. Internal determinants are measured through bank size (KBMI), seasonal periods (Q1–Q4), and the CAMEL framework—Capital Adequacy Ratio (CAR), Non-Performing Loans (NPL), Good Corporate Governance (GCG), Operational Efficiency (BOPO), and Loan-to-Deposit Ratio (LDR)—while external determinants include GDP growth, inflation, unemployment rate, consumer and business confidence indices, Bank Indonesia rate, exchange rate, and COVID-19 period. The results indicate that credit quality (NPL), intermediation efficiency (LDR), seasonal periods, and bank scale (KBMI) significantly affect profitability (ROA) and quarterly earnings per share (QEPS). Externally, consumer confidence, business optimism, and employment conditions play a supporting but secondary role. Overall, the findings highlight that sustainable profitability in Indonesia’s major banks is driven primarily by internal management efficiency, prudent risk governance, bank scale, and adaptive response to macroeconomic fluctuations, providing valuable insights for regulators, investors, and policymakers in maintaining financial stability and shareholder value.